Level of the information ecosystem of an educational institution and the impact of the digitization process on its development. - Loiko, Valeriia; Butenko, Andriy; Teremetskyi, Vladyslav; Serohina, Svitlana; Sukhomlyn , Viktor (Journal of the University of Zulia, 2022)
The purpose of the article is the formation of methodological recommendations, an algorithm for determining the level of an educational institution’s information ecosystem and the identification of the essence of the impact of the digitalization process on its development and transformation. The research methods used are monographic analysis, analysis and synthesis, systemic, economic-mathematical modeling, generalization. It has been substantiated that modern information ecosystems of educational institutions in Ukraine are in the process of formation and the development of their information ecosystem is affected by the process of digitalization. It has been concluded that a person of a new formation is formed due to the improvement and acquisition of new digital skills. Those skills are the basis of professional activity and a vital necessity for a person of a new formation. It has been emphasized that there is a change in the education system – transition from passive learning by listening to active learning by searching and studying information, sharing knowledge and skills under the influence of the digitalization process.